(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acne vulgaris is a chronic inflammatory dermatosis of the pilosebaceous follicle, which affects approximately 80-85% of adolescents (13-18 years), mostly males; prevalence that is reversed in adults: 3% in males and 11-12% in females. Our research is evaluated the clinical outcomes of acne vulgaris in children, as well as it enrolled improvements of patients after treatment. A cross-sectional study was performed into children with acne vulgaris and who undergone to treatment at Karbala, Iraq, during a 12-month follow-up period among May 2024 to May 2025. Based on the global acne grading index scoring, the severity of acne lesions was classified into form categories: grade 1, grade 2, grade 3, and grade 4. All patients were undergone to different several therapies, which are (Tretinoin & Adapalene), (Benzoyl Peroxide (BPO)), (Clindamycin & Erythromycin), and Oral Isotretinoin. According to the quality of life assessment, we performed a questionnaire to evaluate patients’ quality of life through three DLQI, PedsQL, and ASQoL, distributed into evaluating the performance of each therapy, their impact on patients. This study found that family history of acne had on of a risk factors which effect on patients, including 68.6 %, the severity acne with grade 2 had 42.90% and severity acne with grade 3 had 35.70%, which almost comedones was prevalence into with all grades on 100% patients alongside with it was located in face of 78.6 % patients and aggravating factors were cosmetic/oily products had 71.4%, menstrual cycle in females had 64.9%, and stress had 54.3%. Based on treatment management, we noted that (tretinoin & Adapalene) had almost has shown superior improvement in the treatment of patients with skin’s patients, although all other therapies could also managed patients. Based on the Cardiff Acne Disability Index (CADI) questionnaire, this study shown the functional impact of (Tretinoin & Adapalene) has 0.9 ± 0.5. Based on the DLQI questionnaire, it also shown 2.1 ± 1.5 during 12 months follow-up after treatment. The current study indicates the dramatic improvement in patients’ quality of life following successful interventions for treating childhood acne, including psychological, physical, and self-esteem aspects.